Structural and electronic properties of graphene and modified graphene - Zhan, Da (2013)
In this thesis, I will mainly focus on using Raman spectroscopy and imaging to probe the electronic and crystal structures of graphene that modified both chemically and physically. This thesis is divided into five parts. The first part covers Chapter 1. It reviews the progress on modification of graphene's electronic structure, and introduces the relationship between Raman features and graphene's properties. For modification of graphene's electronic structure, I review some important and common methods, which include applying external electric and magnetic field, changing stacking status, defects, and strain. The second part (Chapter 2) introduces the investigation of graphene edge thermal dynamics. As controlling edge chirality of graphene nanoribbon can tune its electronic structure, and thus it is of great importance to understand the thermal annealing effect on graphene edges as it is one of the inevitable processes for nano device fabrication. In my studies, the armchair edges present much better thermal stability compared to zigzag edges, while the zigzag edges are not thermal stable as revealed by the activation of Raman D band after annealing treatment. The edge atomic structure evolution under annealed at different temperature (from 200 to 500°C) is also studied in detail by comparing the polarized Raman intensity ratio ofD and G bands. In the third part (Chapter 3), the edge dynamics ofbilayer graphene is presented. Motivated by one of the most influentially reported result that the AB-stacked bulk graphite is structurally modified to many AA-stacked bilayer graphene with closed edges at both armchair and zigzag edges after anneal at extremely high temperature (2000 °C) (Phys. Rev. Lett. 102, 015501, 2009), I carried out the work for low temperature edge dynamics study. Based on the conclusions I obtained from single layer graphene edge thermal dynamics, it is indirectly discovered by Raman image and spectroscopy that the zigzag-edge of bilayer graphene is preferred to form closed state when it anneals at low temperature. The formation of closed zigzag edges of bilayer graphene is also supported by the dramatically decreased system energy as revealed by DFT calculation. The armchair edges of bilayer graphene cannot form closed state because of geometrical incompatibility. Hence the thermal dynamic behaviour of the armchair edges of bilayer graphene can be considered as two independent armchair edges oftwo layers. The fourth part (Chapter 4 and 5) introduces the Raman studies ofFeCh-based full intercalation few-layer graphene compounds. Both evolutions of G and 2D bands are discussed in details for identification ofthe modified few-layer graphene crystal structure. The electronic properties of such compound are discussed by its 2D band features. The theoretical calculation results are used to assist the explanation of its Raman features and electronic properties. Followed by the preliminary characterization, various laser energies as excitation source to probe the Raman scattering features for this compound, and the laser dependent G band intensity for graphene layers doped in different level is observed. The mechanism for the enhancement of Raman G band for some specific graphene layers is also revealed theoretically. The fifth part (Chapter 6) introduces another kind of FeCh-based trilayer graphene intercalation compounds. In this type compound, only ·one interlayer space of the trilayer graphene is intercalated and the other interlayer space keeps unchanged. The intercalated FeCh separates the pristine trilayer graphene into two independent parts, which are single layer graphene and bilayer graphene, respectively. This kind of abnormal compound presents obvious different Raman features compared to the full intercalation case. The electronic band structure of this new type intercalation compounds also exhibits exotic property for its opened bandgap arising from inversion symmetry breaking of the separated bilayer graphene.